Complex spatio-temporal structure of the Holocene Thermal Maximum - Cartapanis, Olivier; Jonkers, Lukas; Moffa-Sanchez, Paola; Jaccard, Samuel L.; De Vernal, Anne (Nature Communications, 2022)
Abstract Inconsistencies between Holocene climate reconstructions and numerical model simulations question the robustness of climate models and proxy temperature records. Climate reconstructions suggest an early-middle Holocene Thermal Maximum (HTM) followed by gradual cooling, whereas climate models indicate continuous warming. This discrepancy either implies seasonal biases in proxy-based climate reconstructions, or that the climate model sensitivity to forcings and feedbacks needs to be reevaluated. Here, we analyze a global database of Holocene paleotemperature records to investigate the spatiotemporal structure of the HTM. Continental proxy records at mid and high latitudes of the Northern Hemisphere portray a “classic” HTM (8–4 ka). In contrast, marine proxy records from the same latitudes reveal an earlier HTM (11–7ka), while a clear temperature anomaly is missing in the tropics. The results indicate a heterogeneous response to climate forcing and highlight the lack of globally synchronous HTM.

A global database of Holocene paleotemperature records - Kaufman, Darrell; McKay, Nicholas; Routson, Cody; Erb, Michael; Davis, Basil; Heiri, Oliver; Jaccard, Samuel; Tierney, Jessica; Dätwyler, Christoph; Axford, Yarrow; Brussel, Thomas; Cartapanis, Olivier; et al. (Scientific Data, 2020)
Abstract A comprehensive database of paleoclimate records is needed to place recent warming into the longer-term context of natural climate variability. We present a global compilation of quality-controlled, published, temperature-sensitive proxy records extending back 12,000 years through the Holocene. Data were compiled from 679 sites where time series cover at least 4000 years, are resolved at sub-millennial scale (median spacing of 400 years or finer) and have at least one age control point every 3000 years, with cut-off values slackened in data-sparse regions. The data derive from lake sediment (51%), marine sediment (31%), peat (11%), glacier ice (3%), and other natural archives. The database contains 1319 records, including 157 from the Southern Hemisphere. The multi-proxy database comprises paleotemperature time series based on ecological assemblages, as well as biophysical and geochemical indicators that reflect mean annual or seasonal temperatures, as encoded in the database. This database can be used to reconstruct the spatiotemporal evolution of Holocene temperature at global to regional scales, and is publicly available in Linked Paleo Data (LiPD) format.